2019
DOI: 10.1158/1055-9965.epi-18-0935
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cancer Pleiotropic Associations with Lung Cancer Risk in African Americans

Abstract: Background: Identifying genetic variants with pleiotropic associations across multiple cancers can reveal shared biologic pathways. Prior pleiotropic studies have primarily focused on European-descent individuals. Yet population-specific genetic variation can occur, and potential pleiotropic associations among diverse racial/ethnic populations could be missed. We examined cross-cancer pleiotropic associations with lung cancer risk in African Americans. Methods: We conducted a pleiotropic analysis among 1,410 A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 97 publications
0
17
0
Order By: Relevance
“…54 HAPLN1 is also a susceptibility gene for lung cancer. 55 In RA, Urano et al 56 studied the correlation between HAPLN1 gene polymorphism and spinal degenerative changes in 622 post-menopausal Japanese women and showed that mutations in the specific HAPLN1 loci are related to spinal degeneration. Furthermore, genome-wide association analysis reported HAPLN1 as one of the important susceptibility genes for ankylosing spondylitis in the Han population.…”
Section: Discussionmentioning
confidence: 99%
“…54 HAPLN1 is also a susceptibility gene for lung cancer. 55 In RA, Urano et al 56 studied the correlation between HAPLN1 gene polymorphism and spinal degenerative changes in 622 post-menopausal Japanese women and showed that mutations in the specific HAPLN1 loci are related to spinal degeneration. Furthermore, genome-wide association analysis reported HAPLN1 as one of the important susceptibility genes for ankylosing spondylitis in the Han population.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) of individual cancer types have also identified loci associated with multiple cancer types, including 5p15 ( TERT-CLPTM1L) 3 , 6p21 (HLA complex) 4 , 5 , and 8q24 6 . Non-GWAS approaches have yielded further pleiotropic cancer risk variants 7 27 , and genetic correlation studies have identified cancer pairs with shared heritability 28 31 .…”
Section: Introductionmentioning
confidence: 99%
“…, 2015 ; Ríos-Tamayo et al , 2016 ; Oh et al, 2017a ; Tong et al., 2018 ) rs11651052 ( Painter et al , 2015 ). Endometrial cancer risk rs11658063 ( Jones et al, 2019 ) CAG (10.8%) -0.95 72.4 0.606 0.9-0.98 TA C (31.5%) -0.96 79.96 0.688 0.92-0.99 TAG (6,8%) -0.95 51.56 0.453 0.89-0.99 BRCA1 TG (69.2%) rs16942 rs1799949 -0.99 101.43 0.868 0.96-1.0 rs16942 ( Cox et al , 2011 ; Heramb et al. , 2015 ; Sagna et al, 2019 ) rs1799949 ( Ricks-Santi et al , 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The present study was based on 35 SNPs that can potentially modify the risk of cancer. A literature research revealed that only 10 of these 35 SNPs were described in studies of African or Afro-American populations ( Mechanic et al, 2007 ; Chornokur et al., 2013b ; Nikolić et al, 2014 ; Oh et al, 2017b ; Oussalah et al, 2017 ; Tong et al., 2018 ; Jones et al, 2019 ; Sagna et al, 2019 ; Song et al, 2019 ; Kamiza et al., 2020 ), suggesting that most association studies including these SNPs focused on European and Asian populations. The present results showed that a high number of individuals were homozygous for risk alleles with Native American and African ancestry that may modify the risk of cancer.…”
Section: Discussionmentioning
confidence: 99%